Outreach of HIV/AIDS Disease on Prisoners at Women Prison of Class IIA Jakarta Timur - Ana, Elsa Fitri; Ardiana, Meta; Yatimah, Durotul; Lestari, Retno Dwi; Wibowo, Setiawan; Darmawan, Daddy (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
This program aims to enhance the knowledge and understanding of inmates regarding HIV/AIDS while also reducing stigma and discrimination within the prison environment. This program is based on data indicating a higher prevalence of HIV among prisoners compared to the general population. The primary challenges faced include a lack of information and education about HIV/AIDS and limited access to healthcare services within the prison. The program’s methodology includes planning activities with clearly defined goals and targets, forming a working team, and developing educational materials. The program’s implementation involves an initial outreach phase, followed by an educational session consisting of lectures and interactive discussions. Monitoring and evaluation are conducted by collecting data and assessing the activities to measure the program’s effectiveness using interview with prisoner and checklist. A total of 25 participants, aged between 21 and 50 years, participated in this program. The results demonstrated active participation and enthusiasm from the inmates (100%), indicating the program’s success in bridging knowledge gaps and reducing stigma. This program has fostered a healthier, safer prison environment and better-prepared inmates for social reintegration with improved health knowledge. It is hoped that this program can serve as a model for other prisons in Indonesia in the efforts to prevent and combat HIV/AIDS.